2018
DOI: 10.4028/www.scientific.net/kem.770.80
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alloying Elements in Fatigue Properties of α/β Titanium Alloys

Abstract: One strategy to make PM titanium components competitive in terms of mechanical properties is the addition of suitable alloying elements. PM offers the possibility to adapt the alloy composition in order to achieve the required properties. In this study, different alloying elements were introduced into α/β titanium alloys and fatigue behaviour was evaluated. Four-point bending fatigue tests with a stress ratio of 0.2 were performed on specimens manufactured by metal injection moulding (MIM) and shot peening. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…E.g. oxygen in a Ti 6Al 4V or Ti 6Al 7Nb alloy appears considerably less critical as implied by standards [16]. It was shown that even values of 0.35 wt.% and higher do not introduce severe embrittlement, although the typical limit according to standards is just 0.2 wt.%.…”
Section: Sintering-based Processing Of Titanium Powdersmentioning
confidence: 96%
“…E.g. oxygen in a Ti 6Al 4V or Ti 6Al 7Nb alloy appears considerably less critical as implied by standards [16]. It was shown that even values of 0.35 wt.% and higher do not introduce severe embrittlement, although the typical limit according to standards is just 0.2 wt.%.…”
Section: Sintering-based Processing Of Titanium Powdersmentioning
confidence: 96%